4CPS-232 Analysis of oral medication prescription and administration through the jejunostomy or the nasogastric tube in an intensive care unit: how to improve patient's hospitalisation?. (2nd March 2018) - Cabaret-Loux, M; Perreux, J; Cavagna, P; Fernandez, C; Lescot, T; Bizet, S; Antignac, M
Abstract : Background: In an intensive care unit (ICU), patients are frequently unable to take oral tablets and capsules due to invasive ventilation or sedation. Therefore medications are administered by nasogastric tube or jejunostomy. Moreover, it is to be expected that massive resection of the gastrointestinal tract will have consequences on the absorption of orally administered medication. Few data or guidelines are available to help physicians and nurses to prescribe and administer drugs to these patients. Purpose: To assess prescriptions and administrations of oral medications through jejunostomy or the nasogastric tube in surgical ICU. Material and methods: We conducted a prospective descriptive study between January and February 2017 among patients with stomy, or nasogastric tube and oral medications prescriptions. Medical data (type of surgical resection), prescription data (drugs) and administration data (modalities of preparation and administration) were collected in medical files and by nurses' interviews by a clinical pharmacist student. Conformity of drugs administrations were assessed regarding preparation solvent, lack of simultaneous mix in the same syringe, administration by nasogastric tube or opening of capsules allowed. Results: Overall, 283 medications were studied for patients presenting an enteral feeding tube or a jejunostomy. Finally, nurses were interrogated about their administration practices for 82 medications to describe the usual process. Concerning the prescription, 18.3% (52/283) of the oral medications were prescribed without indications about specific administration routes (stomy, nasogastric tube or other) when it was necessary and considerations for the digestive resection. Modalities of drugs preparation (solvent) were never prescribed. Regarding administration, habits are very different according to nurses, medications were mainly solved before administration (99%, n=82/83), into sodium bicarbonate (98%, n=81/82). Within those medications, 39% (32/82) were simultaneously administered in the same syringe that was exposed to potential physico-chemical interactions, and could induce reduced efficiency or toxic metabolites. After analysis, 69.5% (n=57/82) of drugs administrations were found to be improper. Conclusion: This study highlights the importance of clear guidelines. After the survey, the pharmacists' team propose administration guidelines. Hence, a pharmacist analyses orders, gives advice via a new individual summary sheet completed according to the patient's gastrointestinal tract resection, examines the possibility of mashing the tablet or opening the capsules and available alternatives. No conflict of interest